An Individual-Differences Approach to Poetic Metaphor: Impact of Aptness and Familiarity. - Stamenković, Dušan; Milenković, Katarina; Ichien, Nicholas; Holyoak, Keith J. (Metaphor & Symbol)
Using poetic metaphors in the Serbian language, we identified systematic variations in the impact of fluid and crystalized intelligence on comprehension of metaphors that varied in rated aptness and familiarity. Overall, comprehension scores were higher for metaphors that were high rather than low in aptness, and high rather than low in familiarity. A measure of crystalized intelligence was a robust predictor of comprehension across the full range of metaphors, but especially for those that were either relatively unfamiliar or more apt. In contrast, individual differences associated with fluid intelligence were clearly found only for metaphors that were low in aptness. Superior verbal knowledge appears to be particularly important when trying to find meaning in novel metaphorical expressions, and also when exploring the rich interpretive potential of apt metaphors. The broad role of crystalized intelligence in metaphor comprehension is consistent with the view that metaphors are largely understood using semantic integration processes continuous with those that operate in understanding literal language.